Celibacy as a Collective Trauma: A Freudian Rereading of Patrick Kavanagh’s The Great Hunger (المجلة الدولية للعلوم التربوية والآداب, 2025)
The Great Hunger (1942) is Kavanagh’s most celebrated poem handling the antipastoral realities of farming life. One major feature of antipastoralism in the poem is the manifestation of a sexually frustrated society. This study focuses on the founding of a psychological interpretation for the issue of celibacy and sexual frustration in Patrick Kavanagh's masterpiece The Great Hunger. Kavanagh counters the pastoral tradition of celebrating a rural community of happy housewives and care free virtuous men. Rather, the poem mainly handles sexual frustration of a society of unmarried men and women. Adopting an interdisciplinary approach, the present paper focuses on the psychological complications, mainly the libidinal and oedipal fixations, associated with and issuing from sexual abstention and frustration. Therefore, an important guide in the working out of the paper's main topic is Freud's Libido and Oedipus complex theories. Integral to the study is an application of Freudian psychosexual symbolism introduced in his The Interpretations of Dreams (1909). Merging also in the study is the role of the church seen as practicing a patriarchal force pertinent to the psychological concerns of the paper.